Enhancing the Quality of Antibodies to HIV-1 Envelope by GagPol-Specific Th Cells - Bonsmann, Michael Storcksdieck Genannt; Niezold, Thomas; Temchura, Vladimir; Pissani, Franco; Ehrhardt, Katrin; Brown, Eric P.; Osei-Owusu, Nana Yaw; Hannaman, Drew; Hengel, Hartmut; Ackerman, Margaret E.; Streeck, Hendrik; Nabi, Ghulam; et al. (Journal of Immunology, 2015)
The importance of Fc-dependent effector functions of Abs induced by vaccination is increasingly recognized. However, vaccination of mice against HIV envelope (Env) induced a skewed Th cell response leading to Env-specific Abs with reduced effector function. To overcome this bias, GagPol-specific Th cells were harnessed to provide intrastructural help for Env-specific B cells after immunization with virus-like particles containing GagPol and Env. This led to a balanced Env-specific humoral immune response with a more inflammatory Fc glycan profile. The increased quality in the Ab response against Env was confirmed by Fc?R activation assays. Because the Env-specific Th cell response was also biased in human vaccinees, intrastructural help is an attractive novel approach to increase the efficacy of prophylactic HIV Env-based vaccines and may also be applicable to other particulate vaccines.
EVALuna2:8276